2020
DOI: 10.1021/acsami.9b18749
|View full text |Cite
|
Sign up to set email alerts
|

Growth of High-Quality Superconducting FeSe0.5Te0.5 Films on Pb(Mg1/3Nb2/3)0.7Ti0.3O3 and Electric-Field Modulation of Superconductivity

Abstract: Heterostructures composed of superconductor and ferroelectrics (SC/FE) are very important for manipulating the superconducting property and applications. However, growth of high-quality superconducting iron chalcogenide films is challenging because of their volatility and FE substrate with rough surface and large lattice mismatch. Here, we report a two-step growth approach to get high-quality FeSe 0.5 Te 0.5 (FST) films on FE Pb(Mg 1/3 Nb 2/3 ) 0.7 Ti 0.3 O 3 with large lattice mismatch, which show superconduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For the film epitaxial growth, one main interaction arises from the mismatch of the in-plane lattice parameters between the film and the substrate. This leads to either a compressive or tensile stress on films. To grow FeSeTe films, most of the substrates used so far, such as CaF 2 , ,, MgO, and SrTiO 3 , , have a larger in-plane lattice parameter compared with that of FeSeTe. However, it has been found that, instead of a tensile stress, all the FeSeTe films exert a compressive stress with a smaller in-plane lattice parameter than those of bulk samples. This has been attributed to the much larger thermal expansion coefficient of the substrates compared with that of FeSeTe films .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the film epitaxial growth, one main interaction arises from the mismatch of the in-plane lattice parameters between the film and the substrate. This leads to either a compressive or tensile stress on films. To grow FeSeTe films, most of the substrates used so far, such as CaF 2 , ,, MgO, and SrTiO 3 , , have a larger in-plane lattice parameter compared with that of FeSeTe. However, it has been found that, instead of a tensile stress, all the FeSeTe films exert a compressive stress with a smaller in-plane lattice parameter than those of bulk samples. This has been attributed to the much larger thermal expansion coefficient of the substrates compared with that of FeSeTe films .…”
Section: Introductionmentioning
confidence: 99%
“…The compressive stress mostly accumulates at the interface, while the film away from the interface tends to recover its bulk lattice value. , Therefore, for thin films, the effect of the substrate is the most obvious, while with increasing thickness the strain energy increases. The balance of the competition is reached when the strain energy of the system equals the energy needed to create a unit length of dislocation, where the film reaches its critical thickness.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, an interface engineering strategy by adopting a nonsuperconducting FST seed layer was also demonstrated to be an effective way to improve the homoepitaxial growth of FST thin films . Furthermore, Mei et al proposed a two-step method for growing high-quality FST thin films that combines the benefits of both high and low deposition temperatures . Specifically, the high deposition temperature promotes good crystallinity but is unfavorable for superconductivity, while the low deposition temperature is unfavorable for crystallinity but beneficial for superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…37 Furthermore, Mei et al proposed a two-step method for growing high-quality FST thin films that combines the benefits of both high and low deposition temperatures. 38 Specifically, the high deposition temperature promotes good crystallinity but is unfavorable for superconductivity, while the low deposition temperature is unfavorable for crystallinity but beneficial for superconductivity. In this paper, we investigate the thickness effect in FST CCs up to 2 μm on IBAD-LMO metal templates.…”
Section: ■ Introductionmentioning
confidence: 99%